Ultrasonic scouring as a pretreatment of wool and its application in low-temperature dyeing. Issue 10 (May 2019) - Pan, Yi; Wang, Wuchao; Gong, Kang; Hurren, Christopher J; Li, Qing
Ultrasonic technology has shown the potential to reduce the cost and environmental impact of textile wet processing. This work investigates the effects of ultrasonic irradiation as a pretreatment on wool and its application in low-temperature dyeing. A significant increase in dye uptake and color strength was observed on the fabric ultrasonically pretreated at 40 kHz, followed by that at 80 kHz and the conventionally treated sample, in both acid dyeing and reactive dyeing. This could be due to the changes of the fiber surface structure and modification of the chemical structure in the cell membrane complex as a result of ultrasonic pretreatment. In acid dyeing, a 20% increase in dye uptake was achieved at 70℃ upon applying ultrasonic pretreatment at 40 kHz. With the assistance of a leveling agent, 80% dye uptake of the fabric treated with ultrasonics at 40 kHz was measured at 70℃ in reactive dyeing. Ultrasonic pretreatment can be applied in raw wool scouring and fabric scouring to achieve an efficient dye uptake, and these are also discussed in this paper.